Eye movement characteristics in schizophrenia: A recent update with clinical implications - Kentaro Morita; Kenichiro Miura; Kiyoto Kasai; Ryota Hashimoto (Wiley, 2020)
Abstract Eye movements are indispensable for the collection of visual information in everyday life. Many findings regarding the neural basis of eye movements have been accumulated from neurophysiological and psychophysical studies. In the field of psychiatry, studies on eye movement characteristics in mental illnesses have been conducted since the early 1900s. Participants with schizophrenia are known to have characteristic eye movements during smooth pursuit, saccade control, and visual search. Recently, studies evaluating eye movement characteristics as biomarkers for schizophrenia have attracted considerable attention. In this article, we review the neurophysiological basis of eye movement control and eye movement characteristics in schizophrenia. Furthermore, we discuss the prospects for eye movements as biomarkers for mental illnesses.